2015
DOI: 10.3892/etm.2015.2663
|View full text |Cite
|
Sign up to set email alerts
|

Effects of paroxetine on spatial memory function and protein kinase C expression in a rat model of depression

Abstract: Abstract. The aim of the present study was to investigate the effects of paroxetine on the spatial memory and expression level of protein kinase C (PKC) in a rat model of depression. Rat models of depression were established by chronic unpredictable mild stress. The spatial learning and memory function of the rats were assessed by the Morris water maze test. The expression levels of PKC in the hippocampus were detected by western blotting. The results showed that, compared with the control group, the escape la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
1
10
0
1
Order By: Relevance
“…S2). We found that thalidomide, paroxetine, and methoxamine increased the percentage of counterclockwise (CCW) cells, suggesting a potential role of PKC in cardiac cell chirality (3134). Moreover, our work from the 2D micropatterning system with clockwise cells such as human umbilical vein endothelial cell (HUVEC) lines (27) demonstrated that the activation of PKC signaling reverses chirality of endothelial cells from clockwise (CW) to CCW (35).…”
Section: Resultsmentioning
confidence: 88%
“…S2). We found that thalidomide, paroxetine, and methoxamine increased the percentage of counterclockwise (CCW) cells, suggesting a potential role of PKC in cardiac cell chirality (3134). Moreover, our work from the 2D micropatterning system with clockwise cells such as human umbilical vein endothelial cell (HUVEC) lines (27) demonstrated that the activation of PKC signaling reverses chirality of endothelial cells from clockwise (CW) to CCW (35).…”
Section: Resultsmentioning
confidence: 88%
“…While a certain extent of standardization of the procedure may be desirable, there are no standard factors that distinguish the laboratories in which the procedure operates reliably from those where it does not (39). Anhedonia is one of the primary symptoms of depression, which can be inferred from a reduction in the intake of sweet liquid food (1,40). As expected, the SPP of rats decreased significantly following the CUMS procedure in the present study, which was consistent with results of a previous study (7).…”
Section: Discussionmentioning
confidence: 99%
“…Depression is a prevalent and recurrent psychological illness that results in a significant burden for individuals and the society (1). Previous studies indicated that electroconvulsive therapy (ECT) is an efficient and rapid treatment for major depression, especially for patients with drug-resistant and refractory depression (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 40 healthy male albino Wistar rats (6-8 weeks old; 230-300 g) were purchased from the Animal Experiment Center of Dalian Medical University (Dalian, China) and maintained under standard conditions (22±2˚C with a 12-h dark-light cycle) and experiments were conducted in accordance with the Guide for the Care and Use of Laboratory Animals adopted by the Institutional Animal Care and Use Committee (11). All rats were fed with regular chow and given free access to water.…”
Section: Animalsmentioning
confidence: 99%